Utilization of e-book among university mathematics students - Letchumanan, Malathi; Ahmad Tarmizi, Rohani (Elsevier, 2010)
This study aims to explore utilization pattern of e-book among mathematics students’ of Universiti Putra Malaysia (UPM). This research adopts simple random sampling method to collect data. About 35 undergraduate students participated in this study. Based on the result, only 37.1% of the respondents have used e-book. Among the reasons given for using e-books are “available around the clock”, “searchable” and “allow easy navigation”. Those who have never used e-books stated that they are not familiar with the technology. The result shows that majority of the respondents like to use e-book for finding materials for their assignments.